2013
DOI: 10.33762/bagrs.2013.111642
|View full text |Cite
|
Sign up to set email alerts
|

Checklists of Gyrodactylus Species (Monogenea) from Fishes of Iraq

Abstract: Surveying the literature concerning the occurrence of the monogeneans of the genus Gyrodactylus parasitizing fishes of Iraq indicated that there are 25 nominated species of this genus on 29 fish species. These are:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…For the Middle East region, there are some generic checklists and faunistic reports that lack comprehensiveness and suggest that Iranian and Iraqi parasite faunas are only weakly investigated (e.g. Pazooki and Masoumian, 2012 ; Abdul-Ameer and Mhaisen, 2013 ; Al-Nasiri, 2017 ; Mhaisen and Abdullah, 2017 ; Mhaisen, 2019 ); they reference outdated studies, do not investigate all regions and host taxa and often fail to consider the taxonomical reclassification of hosts. On the basis of the freshwater parasite fauna studies of fish in Turkey, 60 monogenean species were reported from native fish species (Öktener, 2003 , 2014 ; Cinar, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the Middle East region, there are some generic checklists and faunistic reports that lack comprehensiveness and suggest that Iranian and Iraqi parasite faunas are only weakly investigated (e.g. Pazooki and Masoumian, 2012 ; Abdul-Ameer and Mhaisen, 2013 ; Al-Nasiri, 2017 ; Mhaisen and Abdullah, 2017 ; Mhaisen, 2019 ); they reference outdated studies, do not investigate all regions and host taxa and often fail to consider the taxonomical reclassification of hosts. On the basis of the freshwater parasite fauna studies of fish in Turkey, 60 monogenean species were reported from native fish species (Öktener, 2003 , 2014 ; Cinar, 2014 ).…”
Section: Introductionmentioning
confidence: 99%